Законодавчі основи використання цифрових технологій у закладах загальної середньої освіти - Грицай, Соломія; Горова, Віталіна (Видавництво Львівської політехніки, 2025)
The article examines the legislative framework for the implementation of socio-communication strategies in general secondary education institutions of Ukraine. The key regulatory legal acts regulating the use of digital technologies and online communication tools in the educational process are analyzed.
Keywords: загальна середня освіта; законодавство; соціокомунікаційна стратегія; цифровізація; інформаційні технології; соціальні мережі